Active Spirituality: A Guide for Seekers and Ministers - Groff, Kent Ira (Rowman & Littlefield Publishers, 1993)
A practical guidebook for the inquiring layperson seeking a holistic, intelligent look at the spiritual life, and for the pastor or religious professional seeking a systematic framework and spiritual practices to re-ignite the flame of faith. Groff explains what it means to believe and what to do after you say you believe-through a unique integration of spirituality and service, heart and mind, and various faith traditions. Explore five spiritual disciplines: community, solitude, learning, service, and vocation. Great for study groups.